ANALYSIS OF THE LOCATION OF BUS STOPS ON AMIR TEMUR SHAH STREET (Multidisciplinary Journal of Science and Technology, 2025)
This article lists the requirements for the placement of bus stops by giving them standards. Recommendations have also been made for bus stop deployment, analysis of bus stops through Geo locational information systems, and development of an optimal solution for their deployment.